Eosinophilic Fasciitis: A Case Report and Review of the Literature - Yasemin Turan; Ömer Faruk Şendur; Işıl Karataş-Berkit; Hakkı Arslan; Emel Dikicioğlu-Çetin (Archives of Rheumatology, 2010)
Eosinophilic fasciitis is a rare entity characterized by peripheral eosinophilia, fasciitis and “groove sign”. The characteristic features of this inflammatory disease include scleroderma-like skin indurations, predominantly on the extremities, and peripheral blood eosinophilia. Systemic organs are generally not affected. In this paper, we present the clinical characteristics of a 35-year-old male patient who could not be diagnosed for a long period and was diagnosed as eosinophilic fasciitis following muscle biopsy. We also include herein the results of our literature survey regarding this disease. (Turk J Rheumatol 2010; 25: 208-13)